Kesalahan Siswa Menyelesaikan Permasalahan Berbasis Higher Order Thinking pada Topik Segiempat - iip Ripati Hanipah; Yoppy Wahyu Purnomo (Jurnal Inovasi Pendidikan Dasar, 2018)
The aim of this study was to analyze students’ mistakes in solve higher order thinking skill (HOTS) questions in the quadrilateral topic. The research method was descriptive qualitative. The research subject was three 7th grade students in one of junior high schools in suburbs of Jakarta. The sampling technique was test and interview. The result showed that students were unfamiliar with HOTS questions. The mistakes that was identified were intuitive mistake, algorithm-based mistake, and formal knowledge-based mistake. It was marked by errors in choosing an operation, not paying attention in unit when performing calculations and misconception for the formula.